Awareness of Oral and Maxillofacial Surgery Specialty among Medical Students of a Tertiary Care Centre: A Descriptive Cross-sectional Study - Gurung, Gopal; Pokharel, Mona (Birat Journal of Health Sciences, 2022)
Introduction: Oral and maxillofacial surgery is a relatively young surgical specialty with roots in dentistry and medicine. It has expanded with time from simple extraction of the tooth to the reconstruction of the facial deformity using microvascular free tissue transfer.Objectives: To find out prevalence of awareness of oral and maxillofacial surgery specialty among medical students of Birat Medical College and Teaching Hospital, Nepal.Methodology: A descriptive cross-sectional study was conducted from 1 September 2020 to 30 September 2020. A total of 100 medical students were chosen by convenience sampling method. A semi-structured questionnaire was developed in Google forms and sent to study participants through an internet link to assess the awareness of oral and maxillofacial surgery specialty. Data were analysed by Statistical Package for Social Sciences version 22.Results: The data showed that 81 (81%) of medical students have heard of oral and maxillofacial surgery specialty. Most of the students expected oral and maxillofacial surgeon for treatment of fracture of the lower jaw [86(86%)], upper jaw [89(89%)] and cheekbone [91(91%)].  Many students expected oral and maxillofacial surgeons to treat tumours of jaws [78(78%], cysts of jaws [77(77%)], temporomandibular joint disorders [74(74%)]. Few students expected oral and maxillofacial surgeon for dental implants [16(16%)] and lip repositioning surgery [4(4%)].Conclusion: The majority of medical students have heard of Oral and maxillofacial specialty; however, they are not fully aware of the expertise and potentiality of the specialty.